The Influence of Job Characteristics, Placement, and Leadership Style on Employee Performance of the Ministry of Trade - Agustiasih, Merdika; Marthayudha, Novian Rezka; Wuisan, Dewi (Jurnal Ilmiah Sumber Daya Manusia, 2022)
This study aims to determine whether job characteristics have a positive effect on employee performance, placement has a positive effect on employee performance, and leadership style has a positive effect on employee performance. This research was conducted at the Ministry of Trade of the Republic of Indonesia through a closed questionnaire with a total of 165 employees, using convenience sampling method and Partial Least Square – Structural Equation Modeling (PLS-SEM) analysis. The results showed that there was a positive and significant effect of job characteristics and leadership style on employee performance. Placement has a positive but not significant effect on employee performance. This research is expected to be input for organizations in an effort to improve employee performance through good management of job characteristics, placements, and leadership styles so that they can realize the goals of the organization.